2011
DOI: 10.1002/glia.21213
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bulbar and mucosal olfactory ensheathing cells using FACS and simultaneous antigenic bivariate cell cycle analysis

Abstract: Transplantation of olfactory ensheathing cells (OECs) is a promising route for CNS repair. There have, however, been major discrepancies between the results from different groups. Part of this can be attributed to variations in cell sources and culture protocols. Accurate estimation of the proportions of OECs and their associated fibroblasts (ONFs) and their evolution with time in culture is an essential baseline for establishing the reparative properties of transplants. In this study, we compare the evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…1C). Cytometry analyses were conducted for p75 expression, because this is the only referred marker known to be specifically and differentially expressed in vivo by OECs (Gueye et al, 2011;Kueh et al, 2011;Windus et al, 2010). Intracellular GFAP staining showed that all the p75 cells were GFAP positive, confirming the high purity of the OECs cultures (Supp.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…1C). Cytometry analyses were conducted for p75 expression, because this is the only referred marker known to be specifically and differentially expressed in vivo by OECs (Gueye et al, 2011;Kueh et al, 2011;Windus et al, 2010). Intracellular GFAP staining showed that all the p75 cells were GFAP positive, confirming the high purity of the OECs cultures (Supp.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, because of their specific role during neurogenesis of primary olfactory system, OECs could be found in peripheral nervous system (PNS) and in CNS. Also, it has been previously demonstrated that specific populations of OECs exist in each compartment and that these cells exhibit specific behaviors in vitro and in vivo (Guerout et al, 2010;Kueh et al, 2011;Paviot et al, 2011;Richter et al, 2005;Windus et al, 2010). Specific microenvironment may explain the presence of distinct OECs subpopulations.…”
Section: Introductionmentioning
confidence: 96%
“…GBCs are positive for early neuronal differentiation markers such as Mash1, Neurogenin1, N-CAM, Sox2, and nestin (Gordon et al, 1995;Beites et al, 2005;Thakur et al, 2014), hence confirming that they are neural progenitor cells, while HBCs express keratin 5 and keratin 14 but are negative for neuronal markers (Carter et al, 2004) (see Table 1). However, only specific antibodies GBC-2 and GBC III were used to isolate GBCs from the OE by FACS, according to recent data (Chen et al, 2004;Krolewski et al, 2013;Thakur et al, 2013Thakur et al, , 2014, while ICAM-1 was Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 5/25/15 10:27 PM Human Gorrie et al, 2010;Kachramanoglou et al, 2013;Tabakow et al, 2013;Xie et al, 2013 Rat Rizek andKawaja, 2006;Kalincik et al, 2010;Centenaro et al, 2011;Kueh et al, 2011;Paviot et al, 2011;Stamegna et al, 2011;Tharion et al, 2011;Mayeur et al, 2013;Ishihara et al, 2014Dog Granger et al, 2012Ziege et Rat Kalincik et al, 2010;Centenaro et al, 2011;Paviot et al, 2011;Stamegna et al, 2011;Ishihara et al, 2014 S100 OECs Human Gorrie et al, 2010;Kachramanoglou et al, 2013;Tabakow et al, 2013Rat Centenaro et al, 2011 ( used to purify HBCs (Iwai et al, 2008;Fletcher et al, 2011;…”
Section: Gbcs and Hbcs: Characteristics And Potential Therapeutic Valmentioning
confidence: 99%
“…OM-OECs and OB-OECs present different proliferative capacities (Kueh et al, 2011) and exhibit considerable overlap of antigenic markers in vitro (GarcĂ­a-Escudero et al, 2012). It appears that OM-OECs and OB-OECs display distinct gene expression patterns.…”
Section: Oecs: Great Potential For Sci Repairmentioning
confidence: 99%
“…Microscopic studies of cultured OECs have shown morphologic differences among cultures obtained from lamina propria of nasal mucosa and from olfactory bulb (Kueh et al, 2011;Watanabe et al, 2006). However, there is little evidence regarding morphological ultrastructure particularities in different developmental stages and in different anatomical origins of OECs, including olfactory nerve.…”
Section: Discussionmentioning
confidence: 98%